The Qualities of Tasks in General Chemistry Based on the Analysis of Entrance Procedure at the Faculty of Science, Charles University - Šrámek, Martin; Teplá, Milada (Scientia in educatione, 2022)
This article introduces results of item analysis of chemistry tests used as a part of the admission procedure at the Faculty of Science, Charles University, between 2016 and 2019. The aim of the analysis focusing on general chemistry was to determine which tasks were the most troublesome for applicants and those with a low discrimination index. The troublesome tasks were found based on the calculation of difficult indexes whereas the item discrimination index was represented by ULI(1/2) and RIR coefficients. The results of the item analysis showed that ideal gas law is the hardest and only troublesome topic. Moreover, there were four topics including at least one troublesome item (pH calculation, electron configuration, ion product calculation, and chemical equilibrium). Additionally, the analysis revealed three topics containing an item with a low discrimination index (thermal decomposition, rate law, chemical equilibrium) and, in many cases, its value decreased with a number of steps necessary for reaching the solution in the task.